Prevalence and clinical significance of the genotypic carriage among ESBL phenotype-negative Escherichia coli and Klebsiella pneumoniae clinical isolates in bacteremia: a study in a Malaysian tertiary center - Lau, Chee Lan; Neoh, Hui-min; Periyasamy, Petrick; Tg Abu Bakar Sidik, Tg Mohd Ikhwan; Tan, Toh Leong; Ramli, Ramliza; Naina Mohamed, Isa (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundAntimicrobial resistance (AMR) can lead to fatal consequences. AMR genes carriage by phenotypically susceptible bacteria, such as Extended-Spectrum β-Lactamases (ESBL)s in Enterobacteriaceae, have potential implications for AMR spread and therapeutic outcomes. This phenomenon should be investigated.MethodsPositive blood cultures from hospitalized patients in a Malaysian tertiary center between April 2022 and March 2023 were reviewed. A total of 137 clinical isolates of Escherichia coli (E.coli), Klebsiella pneumoniae (K.pneumoniae), and Klebsiella oxytoca were included. The antibiotic susceptibility and ESBL phenotypes were determined by disk diffusion method and the identification of genotypes by multiplex polymerase chain reaction. The clinical characteristics and outcome information were extracted by reviewing patients’ medical records to evaluate the clinical significance of the ESBL genotype-positive but phenotype-negative isolates in bacteremia.ResultsAll 137 isolates were positive for at least one genotype (blaCTX-M, n = 71, 51.8%; blaSHV, n = 87, 63.5%; blaTEM, n = 95, 69.3%; blaOXA-1, n = 38, 27.7%). While blaCTX-M was proportionately higher in the ESBL phenotype-positive isolates than ESBL phenotype-negative isolates (33/37, 89.2% vs 38/100, 38%; p < 0.001), more than half of those harboring blaCTX-M remained susceptible to third-generation cephalosporins (3GC). The sensitivity (Sen) of blaCTX-M for ESBL phenotypes prediction was 89.19% (95% confidence interval [CI], 74.58 - 96.97%); however, specificity (Sp) was low (46.47%; 95% CI 39.75 - 53.32). The patient characteristics were similar among 98 ESBL phenotype-negative cases, except that the non-blaCTX-M carrier group had significantly more renal impairment (0/37 vs 7/61, p = 0.043) and gastrointestinal sources of bacteremia (9/37 vs 27/61, p = 0.047). No differences were observed in infection severity, in-hospital mortality, and length of stay (LOS) between the blaCTX-M and non-blaCTX-M carrier groups.ConclusionThe current study provides insight into the gene carriage in E.coli and Klebsiella species clinical isolates, including blaCTX-M genotypes in antibiotic-susceptible strains from a Malaysian hospital. The ESBL encoding genotypes such as blaCTX-M presented substantially beyond one-third of the ESBL phenotype-negative or 3GC susceptible E.coli and K.pneumoniae isolated from bloodstream infection. Although clinical outcomes were not worsened with blaCTX-M genotype-positive but ESBL phenotype-negative isolates in bacteremia, the potential implications for AMR spread deserve further investigation.